Synthesis and evaluation of a prodrug of 5-aminosalicylic acid for the treatment of ulcerative colitis - Yan Yan; FengLing Ren; Pengchong Wang; Ying Sun; Jianfeng Xing (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): This study is aimed to design and synthesize a prodrug of 5-aminosalicylic acid and evaluate its ameliorative effect on experimental ulcerative colitis (UC). Materials and Methods: 5-Aminosalicylic acid-alanine (5-ASA-ALA) was synthesized and characterized. Its stability study was conducted in rat plasma and in the gastrointestinal tract environment, its transport characteristic was assessed using the Caco-2 cells. Its colon-targeting property was evaluated by the pharmacokinetic study, and incubation studies. A series of indicators were used to investigate its therapeutic effect on experimental colitis, including the survival rate and body weight of mice, the disease activity index (DAI), the colonic damage score and colon index, the myeloperoxidase (MPO) activity and the levels of malondialdehyde (MDA), total superoxide dismutase (SOD), glutathione (GSH) and glutathione peroxidase (GSH-Px) in colonic tissues. Results: 5-ASA-ALA was barely absorbed in the Caco-2 monolayer or into the rat blood. It was remarkably stable when incubated in the upper gastrointestinal tract, while gradually hydrolyzed in the colon of rats. When orally administered to mice, 5-ASA-ALA had significantly greater therapeutic effect on colitis than the positive control.   Conclusion: 5-ASA-ALA is demonstrated to be a promising oral colon-targeting prodrug of 5-ASA and has potential application in UC treatment.